Predicting kindergartners' end of year spelling ability from their reading, alphabetic, vocabulary, and phonological awareness skills, and prior literacy experiences - Al Otaiba, Stephanie (2010)
The purpose of this paper is to examine the role of home literacy, parental education and demographic factors in addition to conventional literacy skills at the beginning and end of kindergarten in predicting end of kindergarten spelling achievement. The present study involved 9 schools and 29 classrooms serving an economically and ethnically diverse population (n = 288). Students spelled three types of words: sight words, decodable real words, and decodable pseudowords; conventional and invented spellings are reported. Results from a three step hierarchical regression indicated the variables accounted for 66% of the variance in spelling scores, and the single strongest spring predictor was a one-minute letter-sound fluency test. Implications for instruction and for identifying students at risk for future spelling and reading difficulties are discussed.